Exploring patient values in medical decision making: A qualitative study - Lee, Y.K.; Low, W.Y.; Ng, C.J. (Public Library of Science, 2013)
Background: Patient decisions are influenced by their personal values. However, there is a lack of clarity and attention on the concept of patient values in the clinical context despite clear emphasis on patient values in evidence-based medicine and shared decision making. The aim of the study was to explore the concept of patient values in the context of making decisions about insulin initiation among people with type 2 diabetes. Methods and Findings: We conducted individual in-depth interviews with people with type 2 diabetes who were making decisions about insulin treatment. Participants were selected purposively to achieve maximum variation. A semi-structured topic guide was used to guide the interviews which were audio-recorded and analysed using a thematic approach. We interviewed 21 participants between January 2011 and March 2012. The age range of participants was 28-67 years old. Our sample comprised 9 women and 12 men. Three main themes, 'treatment-specific values', 'life goals and philosophies', and 'personal and social background', emerged from the analysis. The patients reported a variety of insulin-specific values, which were negative and/or positive beliefs about insulin. They framed insulin according to their priorities and philosophies in life. Patients' decisions were influenced by sociocultural (e. g. religious background) and personal backgrounds (e. g. family situations). Conclusions: This study highlighted the need for expanding the current concept of patient values in medical decision making. Clinicians should address more than just values related to treatment options. Patient values should include patients' priorities, life philosophy and their background. Current decision support tools, such as patient decision aids, should consider these new dimensions when clarifying patient values.